👤
Danubot2
a fost răspuns

Rezolvaţi în R ecuația: (x – 3)² - 4(2x + 1) = (x – 4) (x + 4) – 7x
Dau coroana!​


Răspuns :

Răspuns: x = 3

Explicație pas cu pas:

(x - 3)² - 4(2x + 1) = (x - 4) (x + 4) - 7x

x²- 6x + 9 - 8x - 4 = x² - 16 - 7x

x²- 14x + 5 = x² - 16 - 7x

- 14x + 5 = - 16 - 7x

- 14x + 7x + 5 = - 16

- 7x + 5 = - 16

-7x = -16 - 5

-7x = -21   |:(-7)  (impartim toata relatia cu -7)

x = 3

#copaceibrainly

Răspuns: x = 3

Explicație pas cu pas:

(x - 3)² - 4(2x + 1) = (x - 4)(x + 4) - 7x

x² - 6x + 9 - 8x - 4 = x² - 16 - 7x

- 6x + 9 - 8x - 4 = - 16 - 7x

- 14x + 5 = - 16 - 7x

- 14x + 7x = - 16 - 5

- 7x = - 21

x = - 21 : (- 7) = 21 : 7 = 3

Mult Succes !